FROM CASH TO QRIS: THE IMPACT OF DIGITAL PAYMENT SYSTEMS ON MICRO ENTERPRISE SALES - Mila Fitri Sundari (GREET, 2025)
This study examines the impact of the Quick Response Code Indonesian Standard (QRIS) on sales performance among micro enterprises in Indonesia, a sector that represents over 99% of national businesses and plays a critical role in employment and economic resilience. Using a mixed-methods design, data were collected through surveys of 200 micro enterprises across the food, retail, and service sectors, complemented by semi-structured interviews with 20 business owners. The quantitative results reveal that QRIS adoption increased average sales by 35% within six months, with the food and beverage sector experiencing the highest growth at 45%. Regression analysis confirms a positive and significant association between QRIS usage and revenue growth (p < .01), while qualitative findings emphasize improved transaction efficiency, enhanced customer loyalty, and greater attractiveness to younger, digitally literate consumers. Despite these benefits, challenges remain in digital literacy, infrastructure, and security. By providing empirical evidence from an underexplored context, this study contributes to the literature on digital financial inclusion and the role of technology in supporting micro enterprise competitiveness. The findings highlight both managerial and policy implications for accelerating inclusive digital transformation in emerging economies.